Cultural differences in planned and impulsive buying, risk aversion, and decision-making in electronics purchases at Helsinki-Vantaa airport. A comparative study of Finnish, Indian, and Turkish travelers. - Poledda, Gian-Carlo (My University, 2026)
This study examines cross-cultural differences in electronics purchasing behavior among Finnish, Indian, and Turkish consumers at Helsinki-Vantaa airport. The study contributes by filling a gap in the limited research on cross-cultural consumer behavior in the underexplored context of airport retail. The research was built upon Hofstede’s cultural dimensions theory and Theory of Planned Behavior (TPB) and Impulsive Buying Theory (IBT). Based on these foundations, the study analyzes how cultural background influences electronics buying decisions of consumers in an airport retail store. In particular, the research focuses on planned versus impulsive buying behavior, self-reward motivation, risk aversion, and independent decision-making. A quantitative cross-sectional design was employed, utilizing self-administered questionnaires collected from consumers who purchased electronics at Helsinki-Vantaa airport. A total of 150 valid responses were obtained, equally distributed among Finnish, Indian, and Turkish respondents. To measure the study’s key constructs including planned buying behavior, impulsive buying decisions, self-reward motivation, risk aversion, and independent decision-making, a 5-point Likert scale was used. The quantitative data were analyzed using SPSS, using descriptive statistics, reliability analysis, and one-way analysis of variance (ANOVA). The findings suggest that cultural background has only limited influence on certain aspects of consumer behavior when buying electronics at Helsinki-Vantaa airport. Finnish consumers showed higher levels of self-reward motivated purchase and demonstrated higher levels of independent decision-making compared to Indian and Turkish consumers. This supports the existing literature suggesting that individualistic cultures prioritize independent decisions and purchases for gratification. Conversely, Indian and Turkish consumers reported higher levels of social influence from family or friends, which supports the literature regarding collectivistic cultures. Turkish consumers were found to emphasize product quality over price more strongly than consumers from Finland and India. However, no statistically significant differences were found on most of the proposed hypotheses. Crucially, the findings indicate that unique situational factors of the airport environment such as, time constraints, emotional state, and special airport-only offers, reduce cultural influences, causing Finnish, Indian, and Turkish consumers to behave more homogeneous regardless of their cultural background. The study contributes to cross-cultural consumer behavior research by demonstrating the interaction between cultural differences and electronics buying behavior in an airport retail store. Additionally, it provides practical implications for airport retailers aiming to optimize their marketing and sales strategies concerning culturally diverse consumers. Moreover, the study offers clear managerial implications for air-port retail managers how they can adapt product assortments, store layouts, price strategies, and in-store communication to more effectively address culturally diverse consumer needs, potentially resulting in higher customer satisfaction and sales.
Keywords: consumer culture; cultural differences; cultural differences; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business